Impact of entrepreneurs' prior experience on their new ventures' early-stage performance: the mediation effect of entrepreneurial mindset level - Chen, Sihui; Zhong, Lichen; Wang, Xiao; Chen, Bolong (Frontiers in Organizational Psychology, 2024)
IntroductionDoes an entrepreneur's prior experience affect the early-stage performance of new ventures? This study further explores the mediating effect of the entrepreneurial mindset, indicated by the quality of business plans, between entrepreneurs' prior experience and the early-stage performance of their new ventures.MethodsThe sample consists of 157 valid formal business plan documents from the “2021 Gusu Science and Technology Angel Program.” The study employs an evaluation system developed to measure the quality of these business plans and assess the entrepreneurial mindset levels.ResultsThe results reveal the mechanism through which prior experience influences early-stage performance. It indicates that entrepreneurs aiming for high long-term new venture performance should focus on learning and acquiring diverse experiences.DiscussionThe opportunity to write and evaluate their business plans can serve as a self-assessment tool for their entrepreneurial mindset using the evaluation system developed in this study. This approach can significantly enhance their performance and contribute to entrepreneurial success. Moreover, by employing this evaluation system, educators and educational institutions can better understand the entrepreneurial mindset levels of trainees (entrepreneurs) and tailor their courses more effectively.